2019
DOI: 10.1021/acssuschemeng.9b01253
|View full text |Cite
|
Sign up to set email alerts
|

Deoxydehydration of Biomass-Derived Polyols with a Reusable Unsupported Rhenium Nanoparticles Catalyst

Abstract: Oxorhenium catalysts effectively transform biomass-derived polyols into corresponding alkenes via deoxydehydration (DODH) with a secondary alcohol as a hydrogen donor. This study describes the preparation of unsupported rhenium oxide nanoparticles (ReO x NPs), their use as DODH heterogeneous catalyst, and changes in the speciation and structure of Re during catalysis leading to a possible mechanism for DODH by a heterogeneous catalyst. The unsupported nanoparticles catalyze various polyols transformation to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 38 publications
4
38
0
Order By: Relevance
“…Abu-Omar and Delferro reported the synthesis of unsupported rheniumo xide nanoparticles (ReO x NPs) from NH 4 ReO 4 and 3-octanol under reflux and their application in DODH catalysis. [38] Glycerol was converted to allyl alcohol in 76 %y ield in 3octanol at 170 8Ca fter 10 h. Ah ot filtration test showedt hat the activec atalysti sh eterogeneousa nd no significant leaching of the catalyst to 3-octanolw as observed, allowing the catalyst to be recycled up to 7times with no loss in activity.T he predominant oxidation-states of Re in the ReO x NPs before catalysis was Re VII with structures similar to perrhenate, after catalysis partial reduction of Re centers to Re V is observed and a higher ratio of Re V and Re VII to lower oxidation-states corresponds to higher catalytic performance. Deuterium labelling experimentss howed al arge KIE for 3-d-octanoli ndicating that CÀHa ctivation during Re reduction is involved in the rate-limiting step.…”
Section: Heterogeneous Rhenium Catalystsmentioning
confidence: 92%
See 1 more Smart Citation
“…Abu-Omar and Delferro reported the synthesis of unsupported rheniumo xide nanoparticles (ReO x NPs) from NH 4 ReO 4 and 3-octanol under reflux and their application in DODH catalysis. [38] Glycerol was converted to allyl alcohol in 76 %y ield in 3octanol at 170 8Ca fter 10 h. Ah ot filtration test showedt hat the activec atalysti sh eterogeneousa nd no significant leaching of the catalyst to 3-octanolw as observed, allowing the catalyst to be recycled up to 7times with no loss in activity.T he predominant oxidation-states of Re in the ReO x NPs before catalysis was Re VII with structures similar to perrhenate, after catalysis partial reduction of Re centers to Re V is observed and a higher ratio of Re V and Re VII to lower oxidation-states corresponds to higher catalytic performance. Deuterium labelling experimentss howed al arge KIE for 3-d-octanoli ndicating that CÀHa ctivation during Re reduction is involved in the rate-limiting step.…”
Section: Heterogeneous Rhenium Catalystsmentioning
confidence: 92%
“…Abu‐Omar and Delferro reported the synthesis of unsupported rhenium oxide nanoparticles (ReO x NPs) from NH 4 ReO 4 and 3‐octanol under reflux and their application in DODH catalysis . Glycerol was converted to allyl alcohol in 76 % yield in 3‐octanol at 170 °C after 10 h. A hot filtration test showed that the active catalyst is heterogeneous and no significant leaching of the catalyst to 3‐octanol was observed, allowing the catalyst to be recycled up to 7 times with no loss in activity.…”
Section: Heterogeneous Rhenium Catalystsmentioning
confidence: 99%
“…Reaction time [h] Denning (2013) [7] 0.0042 24 Sandbrink (2015) [8] 0.13 1 Tazawa (2016) [9] 0.0317 52 Kon (2017) [13] 0.0667 0.33 Lin (2019) [16] 0.0039 24 Jang (2019) [20] 0.0095 10 this work 0.24 0.5…”
Section: Publicationmentioning
confidence: 99%
“…4 DODH reactions convert diols to alkenes (Figure 1) and generally require a metal catalyst, a reductant and a solvent. 5 Metal catalysts that have been successfully explored are rhenium, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] vanadium [24][25][26][27] and molybdenum. [28][29][30][31][32][33][34][35] Rhenium has provided the most efficient and highest yielding catalysts but is the most expensive of the three metals.…”
Section: Introductionmentioning
confidence: 99%